Efektivitas Strategi Guru terhadap Peningkatan Literasi Siswa SDS IT Baruna Sibuhuan - Cantika Barbara; Dahliana Dahliana; Siti Robiah Hasibuan; Reyna Novita; Revi Rizkyana; Siti Romlah; Nur Hayati Siregar (JURNAL ILMIAH RESEARCH STUDENT, 2026)
Low reading interest among elementary school students remains a major challenge in developing a sustainable literacy culture. This study aimed to analyze the effectiveness of teachers' strategies in improving students' literacy at SD S IT Baruna Sibuhuan. The research employed a qualitative approach using a case study method. The participants consisted of classroom teachers and first- and second-grade students. Data were collected through observations, interviews, documentation, and tests, and analyzed using the Miles and Huberman interactive model, including data reduction, data display, and conclusion drawing. The findings revealed that teachers implemented various literacy strategies, including reading corners and classroom libraries, the School Literacy Movement through fifteen-minute reading activities before lessons, weekly literacy-based library visits, shared reading, group discussions, digital learning media, reward systems, and active collaboration with parents. These strategies effectively improved students' reading interest, reading habits, and literacy skills. Their success was supported by school leadership, parental involvement, and adequate facilities, while major challenges included excessive gadget use, limited non-textbook collections, and the need for continuous teacher professional development in literacy programs.